Rape Culture in Classical Athens - Lynch, Suzanne (Institutum Romanum Finlandiae, 2025)
This article examines the concept of 'rape culture' and its applicability to Classical Athens: what is rape culture? Can the term be applied to Athens in the classical period? And how can we determine if Classical Athens was a 'rape culture'?
PUBLISHED
Keywords: sexual violence; rape; rape culture; Ancient Greece; Classical Athens; European History; Greek Literature, History and Culture; History of Gender and Sexuality